Application of Interactive Methods in Teaching Isoprocesses - Elmuradov Rustam Ummatkulovich; Tokhirova Zumrad Zayniddinovna (Peerian Journals Publishing, 2022)
This article presents the results of explaining the topic of the explanatory process to students using the method of problem-based learning, creating a problem situation in the classroom
Keywords: logical thinking; mental creativity; independence, knowledge; skills